2012
DOI: 10.1016/j.mib.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Metalloregulation of Gram-positive pathogen physiology

Abstract: Due to the unique redox potential of transition metals, many of these elements serve important roles as cofactors in numerous enzymes. However, the reactive nature of metal becomes an intracellular threat when these ions are present in excess. Therefore, all organisms require mechanisms for sensing small fluctuations in metal levels to maintain a controlled balance of uptake, efflux, and sequestration. The ability to sense metal ion concentration is especially important for the survival of pathogenic bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 51 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…Neutrophils also play a role in the competition for metals by secreting a protein, calprotectin, that sequesters Mn and Zn (Corbin et al, 2008, Kehl-Fie and Skaar, 2010, Kehl-Fie et al, 2011). Metal toxicity is also employed as part of the macrophage killing arsenal by the delivery of redox active Cu to the phagosomal compartment (White et al, 2009, Wakeman and Skaar, 2011). Genetic studies indicate that, individually and collectively, these mechanisms can have a large impact on the outcome of infection (White et al, 2009, Haley and Skaar, 2011, Hammer and Skaar, 2011).…”
Section: Microbial Adaptation and Acclimation To Metal Ion Limitmentioning
confidence: 99%
“…Neutrophils also play a role in the competition for metals by secreting a protein, calprotectin, that sequesters Mn and Zn (Corbin et al, 2008, Kehl-Fie and Skaar, 2010, Kehl-Fie et al, 2011). Metal toxicity is also employed as part of the macrophage killing arsenal by the delivery of redox active Cu to the phagosomal compartment (White et al, 2009, Wakeman and Skaar, 2011). Genetic studies indicate that, individually and collectively, these mechanisms can have a large impact on the outcome of infection (White et al, 2009, Haley and Skaar, 2011, Hammer and Skaar, 2011).…”
Section: Microbial Adaptation and Acclimation To Metal Ion Limitmentioning
confidence: 99%
“…Studies investigating the effects of iron-restriction upon bacteria have demonstrated a range of physiological responses including increased antibiotic resistance, virulence factor expression as well as induction of biofilm formation [23][26]. We and others have demonstrated that NTHI upregulates iron uptake systems in the middle ear and that NTHI deficient in iron acquisition are less fit to survive in this environment [27]–[30].…”
Section: Introductionmentioning
confidence: 99%
“…During infection, vertebrates sequester essential nutrients from invading pathogens in order to restrict microbial growth in a defence tactic known as nutritional immunity (Kehl‐Fie and Skaar, ; Wakeman and Skaar, ). Bioavailable iron concentrations within the host are particularly limiting due to a number of factors: a physiological pH that results in low iron solubility, storage of iron within iron binding proteins and intracellular localization of iron (Bullen and Griffiths, ; Crichton, ).…”
Section: Introductionmentioning
confidence: 99%